“Há algo a ser dito”: o papel da Arquidiocese de Fortaleza na problemática do solo urbano na década de 1980 - Souza Junior, João Leondenes Facundo de (2024)
The struggle for the right to housing constituted a significant milestone in the contexto of burgeoning social movements in the 1980. In Fortaleza, various organizations, individuals, and institutions immersed in the harsh reality of families migrating from the interior of the state stood out in popular oganization amid issues surrounding disputes over the use and possession of urban land. In this contexto, the Archdiocese of Fortaleza, or the Catholic Church, through its pastoral agentes and structure, became central by participating in this conflict, with housing as a prominent elemento. Thus, the aim of the dissertation is to understand how the Church will shape its actions and constructo its discourse arond this social problem, identifying internal and constructo its discoure aront this social problem, identifying internal and external tensions. In this regard, we seek to teflect using Certeau categories: ehar tactics did the Church employ to intervenr in the dynsmics of urban land use and possession? How dud its reach into the peripheries and its symbolic production relat to struggles constitute elements os manifestation thar highlighted a conflict between the Church and the State? To achieve this, we will use sources from publications originating frim te CNBB of the Northeast Region and the Archdiocese of Fortaleza, such as pastoral letters, booklets, reports, and pastoral noterbook. Assitionally, we will conduct interviews and revisit the repercussions os these issues in the periodicals of thar time.